Gastrointestinal bleeding preceding new-onset atrial fibrillation - results from the nationwide FinACAF study. (19th May 2022) - Jolkkonen, S; Aro, A; Haukka, J; Halminen, O; Putaala, J; Linna, M; Mustonen, P; Hartikainen, J; Airaksinen, J; Lehto, M
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Helsinki and Uusimaa Hospital District Funding The Finnish Foundation of Cardiovascular Research Introduction: Initiation of oral anticoagulation (OAC) in case of a new-onset atrial fibrillation (AF) requires assessment of bleeding history. Gastrointestinal (GI) bleedings are among the most common bleeding events. Purpose: We aimed to assess clinical characteristics and initiation of OAC in patients with new-onset AF and a history of previous GI bleeding. Methods: The Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) study is a nationwide study among AF patients conducted as a retrospective register-based linkage study combining data from several Finnish health care registers. The study population consists of all patients diagnosed with AF between the years 2010-2018 and with laboratory data available. Patients were identified from nationwide primary care and reimbursement registries and hospitalization records. OAC purchases at 90 days from cohort entry were obtained from the National Prescription Register upheld by the Social Insurance Institution of Finland. Results: 134 242 patients from the initial FinACAF cohort were included in this substudy. Of these, 6543 (4.9%) patients had a history of GI bleeding. Those with GI bleeding were more often male (52.6%), older (mean age 76.6 ± 11.4 vs 72.4 ± 13.1 years), and had more comorbidities. They also had lower blood hemoglobin (mean 124.9 ± 21.3 vs 135.8 ± 18.4 g/l) and higher serum creatinine (mean 99.7 ± 75.8 vs 87.5 ± 52.7 µmol/l) levels than patiens without preceding GI bleeding. Furthermore, initiation of OAC medication was less frequent in the GI bleeding group (46.9% vs 58.6%). Patient characteristics of the study population including age, sex, comorbidities, OAC medication and laboratory findings are shown in Figures 1 and 2. Conclusions: Patients with AF and preceding GI bleeding are vulnerable to rebleeding events. This may affect decision-making of clinicians, leading to more infrequent initiation of OAC medications.